Increasing awareness of hypoglycaemia in patients with Type 2 diabetes treated with oral agents. (November 2013) - Barnett, A.H.; Brice, R.; Hanif, W.; James, J.; Langerman, H.
Abstract Hypoglycaemia is the most common acute complication of type 2 diabetes and can limit therapeutic efforts to improve glycaemic control in order to protect against long-term complications. It is a potential side effect of the drugs used to treat diabetes, specifically exogenous insulin or insulin secretagogues. As many people are prescribed these agents, hypoglycaemia is frequent in clinical practice, although patients commonly do not inform their healthcare professional of the problems spontaneously. The impact of hypoglycaemia on the patient and to the healthcare system is significant through reduced treatment satisfaction and adherence, reduced quality of life and serious health consequences. This has financial implications and costs for the patient, the public and the economy at large. The single most important risk factor for hypoglycaemia is previous hypoglycaemia. Prevention depends on appropriate education regarding diabetes management and selfcare, self-monitoring of blood glucose, awareness of factors that may precipitate hypoglycaemia, and an individualized approach to therapy and glycaemic control targets. The purpose of this review is to increase understanding of the impact and consequences of hypoglycaemia, in particular that associated with sulphonylurea therapy, and to highlight areas requiring more attention in order to improve the overall management of people with type 2 diabetes.